Implementasi Praktikum Berbantu LKS Berbasis Keterampilan Proses Sains Terhadap Peningkatan Penguasaan Konsep Dan Sikap Ilmiah Pada Materi Pencemaran Lingkungan - Charyanti, Dewi; Hindriana, Anna Fitri; Nur, Sofyan Hasanuddin (Edubiologica, 2021)
The purpose of this study was to improve the mastery of scientific concepts and attitudes after implementing practical activities assisted by LKS based on science process skills (KPS) on environmental pollution material in grade VII SMP. The research method used a quasi-experimental design with a pretest-posttest control group. The sample used was taken purposively as many as 34 students, which were divided into experimental and control groups. The data collection technique used the LKS validation test, concept mastery test, scientific attitude questionnaire, and documentation. The data analysis technique used descriptive analysis and the average difference test. The conclusions of the study are: (1) the quality of the worksheets based on science process skills is good, this is evidenced by the results of validator validation showing valid without revision, based on the results of mastery of the concept having a value above KKM and based on student and teacher responses that the student and teacher worksheets are very good. (2) There is a significant average difference in concept mastery between the experimental class and the control class after the implementation of practical learning assisted by LKS based on science process skills with the class that helps practicum learning assisted by publisher LKS on Environmental Pollution Material in Class VII SMP Negeri 7 Cirebon City as evidenced by students being able to understand learning, students can apply it in real life and students can solve problems (2) The scientific attitude of students in the experimental class has also increased this is shown in every practicum students always have curiosity, are honest in writing the results of their observations, be objective, critical and open.